สมบัติของคอนกรีตบล็อกที่มีการใช้ขวดพลาสติก Polyethylene Terephthalate (PET) เป็นส่วนประกอบ - บูรณากาญจน์ ภัทรภณ (Thai Journal of Science and Technology, 2019)
Nowadays, there are so many waste plastic bottles in Thailand. This type of waste is difficult to dispose and takes many more years for degradation than other wastes. This research focused on the reduction of plastic bottle waste by an alternative use of PET plastic bottles in concrete blocks for exterior walls in architectural applications. This research aimed to study the factor effecting the dry density, water absorption, compressive strength and thermal conductivity of concrete block containing PET plastic bottles. The products used PET plastic bottles (Type 1) with dimensions: 5 cm diameter, 19.5 cm length, 0.3 mm thickness, 9.6 gram weight with volume of 322 mm3, and PET plastic bottles (Type 2) with dimensions: 5 cm diameter, 18.5 cm length, 0.3 mm thickness, 10 gram weight with volume of 335 mm3 in the dimensions of concrete block: 20 cm width, 30 cm length and 7 cm thickness. Test results when compared to the control concrete block showed that the compressive strength of concrete block containing PET plastic bottles was decreased. Dry density of concrete block containing PET plastic bottles was decreased, while water absorption at 30 minutes and 24 hours of concrete block containing PET plastic bottles was increased. The elasticity of modulus of concrete block containing Type 1 PET plastic bottles was the highest and the modulus of elasticity of concrete block containing Type 2 PET plastic bottles was the lowest. The PET plastic bottles affected the thermal conductivity of concrete blocks depending on the arrangement of PET bottles, in which their performances conformed to the TIS 1501-2541 standard for construction in architectural applications. By comparing the test results of properties with the other concrete block containing PET plastic bottles, the concrete block containing Type 1 PET plastic bottles with three bottle arrangement is the most proper concrete block for exterior wall applications with high dry density and compressive strength, low absorption and thermal conductivity. The results of this research can be used as a guideline for using PET plastic bottles in exterior wall construction for architectural works.